Rola doradztwa w kształtowaniu innowacji w turystyce - Zbigniew Zontek (Problemy Zarządzania, 2013)
The aim of the article is to point out the possibilities for the usage of counselling in innovative development of tourist enterprises in the region. The possibility of creating innovation in tourism and their implementation is dependent on the internal predispositions of companies and external factors. The main determinant of innovation in tourist companies is the creation of a favorable environment by institutions supporting their development. This paper presents the results of research conducted among tourism enterprises in the Southern Sub-region of the Silesian Province. The results show, that the main direction of the support are European Union programs and a creation of cluster initiatives.